ANALISIS SISTEM PENGENDALIAN INTERN PENERIMAAN DAN PENGELUARAN KAS KEDUKAAN PADA ORGANISASI NON PROFIT (STUDI KASUS PADA GEREJA BETHEL INJIL SEPENUH ”BUKIT DOA” SINGARAJA): (Studi Kasus pada Gereja Bethel Injil Sepenuh ”Bukit Doa” Singaraja) - Titus Silvi Sadewi; Made Pradana Adiputra (Universitas Pendidikan Ganesha, 2022)
The purpose of this research is to know the internal control system of grief cash receipts and expenditure on Gereja Bethel Injil Sepenuh “Bukit Doa” Singaraja. This research using qualitative as the type of research with study case approach. Interviews, observation and documentation study are the method of collecting data. The interview was conducted with the Pastor, Treasurer of grief, Grief Coordinator, Grief Vice Coordinator and one of the congregations. The observation conducted by doing direct observe on the grief cash receipts and expenditure system. Documentation Study conducted on GBIS “Bukit Doa” Singaraja profile, grief financial statement, grief fee note. The data analysis technique used is qualitative analysis technique using Miles and Huberman model. This research revealed that the internal control system of grief cash receipts and expenditure of Gereja Bethel Injil Sepenuh “Bukit Doa” Singaraja has not fully met the criteria of risk assessment; control activities; information; communication components, while on the environment control and monitoring component have met the criteria.